Kurkumin Meningkatkan Sensitivitas Sel Kanker Payudara terhadap Tamoksifen Melalui Penghambatan Ekspresi P-glikoprotein dan Breast Cancer Resistance Protein: Curcumin Increased Breast Cancer Cells Sensitivity to Tamoxifen Through Inhibition of P-glycoprotein and Breast Cancer Resistance Protein Expressions - Sianipar, Erlia Anggrainy; Louisa, Melva; Wanandi, Septelia Inawati (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2018)
The decreasing of sensitivity or resistance to tamoxifen occured after long-term treatment in breast cancer. One of the major factor in tamoxifen resistance is over expression of efflux transporter P-glycoprotein (P-gp) and Breast Cancer Resistance Protein (BCRP). Curcumin has known as inhibitor of P-gp and BCRP. The addition of curcumin to the tamoxifen resistant cells is expected to increase the sensitivity of breast cancer cells to tamoxifen. This study aim to know the effect of curcumin in increasing the cell sensitivity to tamoxifen through inhibition of P-gp and BCRP transporter efflux. MCF-7 breast cancer cell line was induced with tamoxifen 1 µM for 10 passage (MCF-7(T)), then cell viability and mRNA expression of P-gp and BCRP were analyzed. To the MCF-7(T) cells, curcumin was given at of 5/10/20 µM with or without tamoxifen for 5 days and cell viability and mRNA expression of P-gp and BCRP were analyzed on day 5th. As positive control, verapamil 50 µM was used as P-gp inhibitor, ritonavir 15 µM and nelfinavir 15 µM were used as BCRP inhibitor. The results showed that MCF-7(T) cells sensitivity to tamoxifen decreased with 11.8 times, the cell viability increased 10.82 fold and mRNA expression of P-gp and BCRP increased 4.04 fold. Then after administration of curcumin with or without tamoxifen for 5 days, the cell viability and the mRNA expression of P-gp and BCRP decreased. As conclusion, curcumin increased the sensitivity of MCF-7(T) to tamoxifen characterized by the decreasing of cell viability and mRNA expression of P-gp and BCRP. However, the administration of combination of curcumin with tamoxifen was more potent than just curcumin. The increased sensitivity was estimated at least partly through the inhibition of P-gp and BCRP mRNA expression by curcumin